Nilai-Nilai Pendidikan Karakter dalam Novel Dear Allah Karya Diana Febi Kajian: Sosiologi Sastra - Endang Afriliya; Gustianingsih; Nurhayati Harahap (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This research is motivated by the importance of character education values to form a strong young generation. Character education has the same essence and meaning as moral and moral education which aims to shape individuals to become good human beings, good citizens and citizens. This study aims to describe the intrinsic elements and character education values contained in the novel Dear Allah by Diana Febi, a literary sociology study. This research is a type of literature study research while the research method used is descriptive qualitative method. Data collection techniques through documentation techniques with reading and recording methods, while data analysis in this study is content analysis. Based on the data analysis that has been done, the results of this study are: the intrinsic elements in the novel Dear Allah consist of theme, character and characterization, plot, setting, point of view, language style and mandate, while related to the value of character education, 18 character education values were found, namely: religious values, honesty, tolerance, discipline, independence, democracy, curiosity, respect for achievement, friendly/communicative, peace-loving, fond of reading, environmental care, social care and responsibility.